2021
DOI: 10.1186/s12889-021-10721-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal stress and depressive symptoms and adolescents’ body mass index: a prospective study

Abstract: Background Growing evidence suggests that maternal mental health issues are associated with (young) children’s weight outcomes. However, most studies have been limited by cross-sectional designs and have been aimed at (younger) children. The current prospective study focuses on the link between maternal mental health (i.e., psychological stress and depressive symptoms) and adolescents’ zBMI development. Methods The participants in the present study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 98 publications
1
8
0
Order By: Relevance
“…The PSS is a self-report questionnaire, and is a global measure of stress that is easy to use. Many studies confirm its reliability and validity in a diversity of settings and in multiple languages [ 74 , 75 , 76 , 77 , 78 , 79 ]. The scale measures a person’s evaluation of stressful situations in the previous month of his or her life.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The PSS is a self-report questionnaire, and is a global measure of stress that is easy to use. Many studies confirm its reliability and validity in a diversity of settings and in multiple languages [ 74 , 75 , 76 , 77 , 78 , 79 ]. The scale measures a person’s evaluation of stressful situations in the previous month of his or her life.…”
Section: Methodsmentioning
confidence: 98%
“…All adolescents attending the first and second grade and their parents were invited to participate in this study by means of an active parental consent procedure. Further details on the study design can be found elsewhere [ 75 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…The PSS is an accessible and effective metric of perceived stress, and has demonstrated utility in understanding the relationship between stress and a myriad of both behavioral and health endpoints ( Golden-Kreutz and Thornton, 2005 , Robles and Garey, 2016 , Whitehead and Bergeman, 2017 , Barutcu Atas and Aydin Sunbul, 2021 ). In addition to predictive value for outcomes specific to the individual completing the PSS, this metric has also proven useful in understanding the role of parental perceived stress in adolescent-related outcomes ( Slaughter and Hamilton, 2020 , Koning and Vink, 2021 , Tara and Turpyn, 2021 ). The role of caregiver behaviors and caregiver perceived stress are salient influences during adolescence; therefore, a PSS assessment that caregivers complete about their own stress has been added to the collected metrics.…”
Section: Updates and Known Issues In The Demographic And Mental Health Assessments In The Abcd Studymentioning
confidence: 99%
“…Specifically, low parental well-being (i.e., more stress and depressive symptoms) may increase the use of easier and shorter-term coping strategies to manage children's eating behaviors, to acquire and prepare meals, and to provide nutrition explanation or nutrition rules in an authoritative way ( Koning et al, 2021a , Koning et al, 2021b , Koning et al, 2021c ). As such, parental stress and depressive symptoms may impact all three overarching dimensions of food parenting, resulting in more coercive control (e.g., using food to manage child emotions or behaviors), less structure (e.g., setting snacking rules, modeling and creating a healthy environmental structure), and less autonomy support (e.g., teaching the adolescent about nutrition, providing feedback with regard to own eating, and explaining certain eating rules; ( Gevers, Kremers, de Vries, & van Assema, 2014 ; Koning et al, 2021a , Koning et al, 2021b , Koning et al, 2021c ; Vaughn et al, 2016 ). In general, structure and autonomy-supportive forms of food parenting practices are regarded as effective as they are associated with more healthy versus unhealthy child eating and weight outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This might have led to increased food parenting challenges. Recent studies among (parents of) adolescents suggest that food parenting practices may also impact food intake and, moreover, the development of disordered eating behaviors in this older age group specifically ( Blaine, Kachurak, Davison, Klabunde, & Fisher, 2017 ; Christensen, 2019 ; Fleary & Ettienne, 2019 ; Koning et al, 2021a , Koning et al, 2021b , Koning et al, 2021c ; Taylor, Ditch, & Hansen, 2018 ). However, to the best of our knowledge, there are no longitudinal studies comparing food parenting practices before and during COVID-19 among parents of adolescents.…”
Section: Introductionmentioning
confidence: 99%